Detection of Formalin in Seafoods at markets and wholesaler-Retailer stores (Case study: Xaythany District and Xaysetha District, Vientiane capital): https://doi.org/10.69692/SUJMRD0901273 - VONGKHAMPHEANG, Chanphone; LORBIAYAO, Bounphak; SULYYA, Somphaphone; KEOVONGSUK, Vadsana; OUDONE, Phetdala (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This study was established to analyze formaldehyde contamination in fresh seafood markets and wholesale-retailer stores Case study: Xaythany District and Xaysetha District, Vientiane capital, such as Tanmexai store (A), Phontongsavang market (B, C), Phonkheng store (D), and Donnoun store (E), with 3 objectives: availability of products, finding the volume of formalin contaminated in seafood, and comparing the amount of formalin in similar seafood in each store. Utilizing the Formalin in Food Test Kit, formalin was examined, and the amount of formalin-contaminated fresh seafood was assessed by measuring the absorption in the UV-Vis Spectrophotometer Carry 50 Bio. The results of a formalin analysis of five fresh seafood stores in Vientiane found that the availability of products from each store is similar, but some are different. The examination results of formalin contamination in 39 seafood samples revealed that 14 samples were contaminated. found in store A was not detectable; found in store B, Portunus pelagicus and Octopus 0.07±0.00 mg/kg 0.25±0.02 mg/kg, respectively; found in store C white shrimp, Portunus pelagicus, Loligo duvauceli 0.29±0.01 mg/kg, 0.15±0.00 mg/kg, 0.35±0.08 mg/kg, respectively; found in store D Portunus pelagicus, oyster, Octopus dollfusi, Loligo duvauceli, white squid and Soft cuttlefish 0.19±0.00 mg/kg, 1.06±0.10 mg/kg, 0.37±0.01 mg/kg, 0.18±0.01 mg/kg, 0.15±0.00 mg/kg, and 0.37±0.01 mg/kg, respectively; found in store E white shrimp, Loligo duvauceli, CrispSquid 0.14±0.00 mg/kg, 0.18±0.00 mg/kg, and 0.08±0.01 mg/kg, respectively. The analysis results showed that the Oyster Form D store contaminated formalin by 1.06±0.10 mg/kg, which is higher than other types of seafood. Of which it exceeded the WHO standard (0.05 mg/kg). If consumers always take seafood that is contaminated with formalin, it may affect the consumer’s health.